Morphology and pigment content of sporophytes and gametophytes of ten fern species (Bangladesh Journal of Botany, 2019)
The morphology and pigment contents of sporophytes and gametophytes of ten fern species were studied. In the morphological study, variations were found in stipe, texture, rachis, fronds and sori of these species. Photosynthestic pigment contents of sporophyte and gametophyte of ten species vary to a great extent. Even sporophyte and gametophyte of same species vary in pigment content. Sporophyte revealed higher chlorophyll content than gametophyte. The highest chlorophyll a and b were found in the gametophyte of Cetarach officinarum Gametophyte of Adiantum flabellatum produced maximum anthocyanin whereas minimum anthocyanin content was found in the sporophyte of Cetarach dalhousiae. The highest carotenoid content was obtained from the gametophyte of Cheilanthus albomarginata. Altitudinal variations were also found to affect morphology and pigment content of sporophytes and gametophytes of ten fern species.